Progressive cervical tumour in an HIV-patient: giant pseudoaneurysm of the carotid artery: a case report. Issue 7 (28th June 2022) - Fraund-Cremer, Sandra; Bernd, Rouven; Cremer, Jochen; Rusch, Rene
Abstract: Background: Aneurysms of the extracranial carotid artery are a rare entity and correspond to <1% of all arterial aneurysms. Case summary: A 58-year-old male with known human immunodeficiency virus (HIV) infection presented in the emergency department with a massive cervical tumour on the right side of the neck and a severe occipital pain. Contrast computed tomography demonstrated a pseudoaneurysm of the proximal right internal carotid artery (ICA). Open surgery of the ICA was performed with reconstruction of the posterior vessel wall, embolectomy of the ICA, and anterior pericardial patch reconstruction. After an uneventful postoperative course, the patient was readmitted 4 weeks later with a right retrobulbous haematoma caused by a carotid cavernous fistula. Therefore a coil-embolization of the fistula and finally of the distal right carotid artery was performed. Discussion: In patients with a proven HIV infection, the occurrence of a vasculopathy in the extra- or intracranial carotid artery is significantly increased and the second most common site after the lower extremities. In patients with progredient neck swelling it should be considered in the differential. Surgical therapy is the preferred treatment strategy in the extracranial aneurysm type, especially in this patient collective.